2021
DOI: 10.1108/ijopm-07-2020-0469
|View full text |Cite
|
Sign up to set email alerts
|

How does reverse factoring affect operating performance? An event study of Chinese manufacturing firms

Abstract: PurposeAs a popular supply chain finance (SCF) strategy, reverse factoring has been widely adopted by buyer firms. However, the extant literature provides scant empirical evidence on the performance effect of reverse factoring. The purpose of this study is to seek to narrow this gap by empirically examining the relationship between reverse factoring and operating performance and the contingency conditions of this relationship.Design/methodology/approachBased on a sample of 167 announcements of reverse factorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…They demonstrated that SCF can effectively mitigate the risks contained within a supply chain and can generate a positive effect on a firm's performance, which has been already proven in early modelling works (e.g., Sokolinskiy et al (2018); Yang and Birge, 2018). Furthermore, Shou et al (2021) investigated the relationship between RF and operating performance and the related contingency conditions embedded in this relationship based on a sample of 167 Chinese companies who claimed to have implemented RF to finance suppliers. Shou et al (2021) discovered that RF positively affects the firms' operating margin and cost-efficiency.…”
Section: Scf Performance Outcomes Dimensionmentioning
confidence: 80%
See 1 more Smart Citation
“…They demonstrated that SCF can effectively mitigate the risks contained within a supply chain and can generate a positive effect on a firm's performance, which has been already proven in early modelling works (e.g., Sokolinskiy et al (2018); Yang and Birge, 2018). Furthermore, Shou et al (2021) investigated the relationship between RF and operating performance and the related contingency conditions embedded in this relationship based on a sample of 167 Chinese companies who claimed to have implemented RF to finance suppliers. Shou et al (2021) discovered that RF positively affects the firms' operating margin and cost-efficiency.…”
Section: Scf Performance Outcomes Dimensionmentioning
confidence: 80%
“…Furthermore, Shou et al (2021) investigated the relationship between RF and operating performance and the related contingency conditions embedded in this relationship based on a sample of 167 Chinese companies who claimed to have implemented RF to finance suppliers. Shou et al (2021) discovered that RF positively affects the firms' operating margin and cost-efficiency. Again, these results match with the early theoretical conclusions (e.g., Liebl et al (2016); Kouvelis and Xu, 2021).…”
Section: Scf Performance Outcomes Dimensionmentioning
confidence: 99%
“…The trade credit enables firms pay in advance its liabilities to suppliers who devote to green manufacturing (Parida et al, 2021; Vliet et al, 2015), which promotes their confidence in participating such sustainable activity. In this case, the establishment of collaborative relationship with suppliers becomes more easily, which ultimately nurtures a solid GSI (Shou et al, 2021). Moreover, the application of SCF in the field of sustainability arouses the environmental awareness of suppliers.…”
Section: Theory Foundation and Hypothesesmentioning
confidence: 99%
“…Although some prior research has pointed to the reluctance of suppliers to adopt SCF (Wuttke et al, 2016(Wuttke et al, , 2019, the literature has primarily focused on the large, focal firm perspective, placing less emphasis on their supply chain partners (e.g. Wuttke et al, 2013b;Caniato et al, 2016;Guida et al, 2021;Shou et al, 2021), especially on SMEs. Yet the apparent reluctance to adopt SCF on the part of suppliers is also important to focal firms as the successful implementation of SCF is determined by the degree of participation and frequency of transactions with suppliers and distributors (Dunn, 2011;Hofmann and Zumsteg, 2015).…”
Section: Introductionmentioning
confidence: 99%